EFFECTIVE ORGANIZATION OF MANAGEMENT OF A MODERN HOUSING STOCK - Berdiyeva Dilfuza Akhatovna (American Journals, 2025)
This article includes the classification of types of modern housing stock and the effective organization of management. The main components of the housing problem in the Republic of Uzbekistan, problematic situations of a complex nature of the housing stock were identified. The main tasks for achieving the effective development of the modern housing stock were identified. In conclusion, the main tasks for the effective development of the modern housing stock were identified. Proposals for the effective organization of management of the modern housing stock were developed.